Drive-Leg Kinematics During the Windup and Pushoff Is Associated With Pitching Kinetics at Later Phases of the Pitch. Issue 5 (April 2022) - Fava, Anthony W.; Downs Talmage, Jessica L.; Plummer, Hillary A.; Oliver, Gretchen D.
Background: Inconsistent findings exist between drive-leg ground-reaction forces (GRFs) and pitching mechanics. Previous literature has largely reported drive-leg mechanics and GRFs at the start of the pushoff phase for their role in initiating force development. Little research has assessed drive-leg kinematics that includes a pitcher's windup motion to determine its effects on subsequent phases in the pitching motion. Purpose/Hypothesis: The primary aim was to analyze the relationship between drive-leg knee valgus angle during the windup and subsequent pitching mechanics. We hypothesized that the drive-leg knee valgus angle during the early portion of the pitching motion would alter later phases' pitching mechanics. A secondary aim was to assess GRFs to determine if the drive-leg knee valgus angle was associated with changes in force. We hypothesized that an increased drive-leg knee valgus angle would increase GRFs during the pitching motion. Study Design: Descriptive laboratory study. Methods: A total of 17 high school baseball pitchers (mean age, 16.1 ± 0.9 years; mean height, 180.0 ± 4.8 cm; mean weight, 75.5 ± 7.5 kg) volunteered for the study. Kinematic data and GRFs were collected using an electromagnetic tracking system and force plates. Pitchers threw maximal-effort fastballs from a mound at regulation distance. The drive-leg knee valgus angle was analyzed during the windup and pushoff phases of the pitch to determine its effects on other biomechanical variables throughout the pitching motion. Results: There was a significant relationship between drive-leg knee valgus angle during the windup ( Fchange 1, 12) = 16.13; P = .002; R 2 = 0.695) and lateral GRF in the arm-cocking phase. Additionally, there was a significant relationship between drive-leg knee valgus angle during pushoff ( Fchange (2, 11) = 10.21; P = .003; R 2 = 0.716) and lateral GRF in the arm-cocking phase and pitching-elbow valgus moment in the acceleration phase. Conclusion: Drive-leg knee valgus angle during the windup and pushoff had a significant relationship with drive-leg GRF and pitching-elbow valgus moment at later stages of the pitching cycle. Clinical Relevance: Assessments of drive-leg kinematics during the windup and pushoff may be useful in identifying inefficient movement patterns that can have an effect on the direction of a pitcher's drive-leg force contribution, which can lead to increased forces on the throwing elbow.